Alkaline anion exchange membrane degradation as a function of humidity measured using the quartz crystal microbalance. (2nd March 2017) - Bharath, V.J.; Jervis, R.; Millichamp, J.; Neville, T.P.; Mason, T.; Tjaden, B.; Shearing, P.R.; Brown, R.J.C.; Manos, G.; Brett, D.J.L.
Abstract: The solid polymer electrolyte (SPE) alkaline anion exchange membrane (AAEM) fuel cell exhibits facile oxygen reduction reaction (ORR) kinetics and has the ability to utilise non-precious metal electrocatalysts. However, the AAEM is reported to suffer from increased instability within the alkaline media (degradation) via a number of routes, including nucleophilic elimination when operated at temperatures above 60 °C, somewhat eliminating the kinetic advantage of operating at higher temperatures. Nonetheless, modelling studies have indicated that the membrane hydration could show improved resistance to alkaline instability and subsequent degradation when operated at elevated temperatures. This investigation uses the quartz crystal microbalance (QCM) to examine the thermal stability of a commercial AAEM as a function of humidity. The results show that hydration improves ionomer resistance to degradation, as the ions within the system (namely the OH − nucleophile and cationic headgroups) become less reactive. In-line mass spectrometry data confirms that the ionomer degrades during the elevated temperature excursions used in this study. Graphical abstract: Highlights: AAEM degradation measured using a quartz crystal microbalance. Increased membrane hydration reduces membrane degradation. Ion solvation screens reaction and reduces nucleophilic attack. Degradation products at elevated temperature identified by off-gas analysis.